2018
DOI: 10.2478/eko-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

Content of Plastid Pigments in the Needles of Pinus Pallasiana D. Don in Different Forest Growth Conditions of Anti-Erosion Planting

Abstract: The influence of different forest growth conditions on the content of plastid pigments in Pinus pallasiana D. Don needles in the anti-erosion planting of the steppe zone of Ukraine was investigated. The reduction in the total chlorophyll a and b concentration in the pine needles in the area with insufficient water supply (xerophilous and mesoxerophilous hygrotopes) was found, compared with more favourable conditions for water supply (mesophilous hygrotope). The reduction in the content of green pigments in ari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The peculiarities of pigment accumulation in conifers during the vegetation period are also confirmed by other studies: the most intensively this process takes place in May (Titova, 2013;Bessonova, Ponomar' ova, 2017), the smallest number is observed in September (Zarek, 2016;Deligöz et al, 2018). Our data also proved the previously statements (Kvilala et al, 2014;Verma, Chandra, 2014;Starikova et al, 2016Bessonova, Grytsay, 2018 on the overall decrease in the number of chlorophylls in plant photosynthetic apparatus under stress.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The peculiarities of pigment accumulation in conifers during the vegetation period are also confirmed by other studies: the most intensively this process takes place in May (Titova, 2013;Bessonova, Ponomar' ova, 2017), the smallest number is observed in September (Zarek, 2016;Deligöz et al, 2018). Our data also proved the previously statements (Kvilala et al, 2014;Verma, Chandra, 2014;Starikova et al, 2016Bessonova, Grytsay, 2018 on the overall decrease in the number of chlorophylls in plant photosynthetic apparatus under stress.…”
Section: Discussionsupporting
confidence: 91%
“…In a number of articles (Miron, Sumalan, 2015;Mikhailova et al, 2017;Afanas' eva, 2018;Bessonova, Grytsay, 2018), it has been shown that chlorophyll reacts sensitively to all changes in the metabolism and, in adverse conditions, changes in its total content (a + b) and the ratio of individual forms (a/b). As for such an indicator the amount of chlorophylls (a + b) we should note that the results of author's research in general are the same as others: in the needles of P. abies from Ussuriisk, it was 1.11-1.38 mg/g of wet weight (Titova, 2010), and in the needles of P. pungens from the city of Dnipro (Ukraine), it was 0.99-1.7 mg/g of wet weight (Bessonova, Ponomar' ova, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The research was conducted in Ravine Viyskovyi, which is located on the right side of the Dnipro river near Viyskove village in Solonyansky district of the Dnipropetrovsk region. It preserved both natural forest phytocenoses and artificial anti-erosion forest stands (Bessonova et al, 2015(Bessonova et al, , 2018a.…”
Section: Methodsmentioning
confidence: 99%
“…One of the main problems of modern biology is to identify the impact of environmental stresses on plant organisms (Bessonova, Grytsay, 2018;Bessonova, Ponomar' ova, 2017;Fedorchak, 2020, Mareri et al, 2022. Environmental physiology, which has been actively developing recently, deals with the study of adaptive changes and the course of physiological processes that occur under their influence.…”
Section: Introductionmentioning
confidence: 99%